THE INFLUENCE OF SLOW RELEASE FERTILIZER UREA-ZEOLITE-HUMIC ACID (UZA) TO PADDYS PRODUCTIVITY VARIETY CIHERANG - Pratomo, Kurniawan Riau; Suwardi, Suwardi; Darmawan, Darmawan (Jurnal Zeolit Indonesia, 2009)
Slow Release Fertilizer (SRF) is a modification fertilizer which aims to improving subtances efficiency on fertilizers by organizing the release slowly or gradually. The methods which used to made a SRF has any variety such as enlarging size, smoothing fertilizer surface, mixing with another difficult soluble materials, and covering fertilizer with certain ingredients so releasing fertilizer under soil more slowly. Some materials can be used as SRF materials are zeolite and humic acid. Zeolite is a silicate mineral which have a high cation exchange capacity (CEC) (varying between 80-180 meq/100g), fit hollow space to ammonium ion size so it have high adsorption capacity to ammonium ion. Meanwhile, humic acid which extracted from inorganic materials has a high CEC too. In this study, urea fertilizer has easily lost characteristics because of leaching and evaporation was conducted by covering zeolite and humic acid. The study aimed to find a proper dosage from combinations of urea, zeolite, and humic acid (UZA) for the paddy and to find proper applications of UZA for paddy. The experiment was conducted in green house with paddy variety Ciherang as an indicator plant. Paddy was fertilized with a standard dosage of N fertilizer from UZA with humic acid value of 0%, 1%, 2%, 3%, 4%, and 5%. UZA fertilizer can improving paddy growth and productivity. UZA fertilizer with 1% humic acid dose is a the best dosage for paddy. The spread distribution of UZA was better than buried on the mud.